Analisis Pemahaman Konseptual Bangun Ruang Siswa Kelas V di MI Safinatun Najah - Dewi Tri Lestari; Cahya Amalia Chusna; Armiya Nur Lailatul Izzah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the level of conceptual understanding of fifth-grade students at MI Safinatun Najah regarding solid geometry, identify conceptual errors that arise, and analyze factors influencing their understanding. The method used is a qualitative approach with a descriptive design. The subject involved 12 students selected based on high, medium, and low understanding categories, along with the fifth-grade mathematics teacher. Data were collected through semi-structured interviews, observations, and document studies. Analysis was conducted through data reduction, data presentation, and conclusion drawing accompanied by verification. The results showed significant variation in students’ conceptual understanding. Some students could explain the elements of solid geometry and relate them to contextual problems, while others were still trapped in rote memorization of formulas. The findings also revealed that procedural skills were more dominant than conceptual understanding, and concrete as well as visual media played an important role in strengthening comprehension. This study indicates that students’ understanding is not uniform but influenced by both internal and external factors. Therefore, learning strategies based on manipulative and contextual media are necessary to improve the quality of their understanding.